Voltage-Aware Time Synchronization for Wireless Sensor Networks. (14th July 2014) - Jin, Meng; Fang, Dingyi; Chen, Xiaojiang; Yang, Zhe; Liu, Chen; Yin, Xiaoyan
The low-cost crystal oscillators in wireless sensor networks are prone to be affected by their working conditions such as voltage, temperature, and humidity. Such effect is often ignored by existing time synchronization solutions that typically assume the frequency error of a given node to be constant and hence adopt frequent timestamp exchanges, resulting in high energy consumptions. We propose a novel voltage-aware time synchronization (VATS) scheme that is inspired by the fact that the clock skew is highly correlated to voltage supplies. VATS features a two-phase process: (i) it first estimates the clock skew and updates the frequency error autonomously based on the local voltage level; (ii) it then adjusts the resynchronization intervals dynamically according to a given synchronization error controlling factor and the synchronization error accumulating rate to balance the calibration accuracy and cost. Since VATS leverages voltage measurements to assist clock skew estimation, it does not require frequent timestamp exchanges as in traditional schemes. Extensive simulation results illustrate the superior performance of the proposed method in terms of calculation accuracy, robustness, and reduced timestamp exchanges for energy saving.